BUMDes as an Arena for Contesting Local Economic Policies: A Review of Village Government Politics in Enrekang Regency - Hardianto Hawing; Hamrun Hamrun; Abdul Karim; Yudhi Abdi Wibowo (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
Village-Owned Enterprises (BUMDes) are designed as strategic instruments to strengthen local economic development and increase village independence. However, in practice, village-owned enterprises function not only as economic entities but also as arenas for policy contestation involving power relations within village government. This study aims to analyze village-owned enterprises as an arena for local economic policy contestation by examining the political dynamics of village government in Enrekang Regency. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews, participant observation, and documentation studies. The results show that the process of formulating and implementing village-owned enterprise policies is influenced by the interaction of interests between the village head, village officials, the village consultative body, and local elites. This contestation has resulted in weak management professionalism, limited community participation, and the suboptimal contribution of village-owned enterprises to village economic growth. This study also found that strengthening participatory governance, institutional accountability, and digital-based transparency has the potential to reconstruct the role of village-owned enterprises as instruments for inclusive and sustainable local economic policy.